2018
DOI: 10.1111/bjh.15525
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab‐mediated haemostatic function in patients with haemophilia A is down‐regulated by activated protein C through inactivation of activated factor V

Abstract: Activated protein C (APC) inactivates activated factor V (FVa) and moderates FVIIIa by restricting FV cofactor function. Emicizumab is a humanized anti-FIXa/FX bispecific monoclonal antibody that mimicks FVIIIa cofactor function. In recent clinical trials in haemophilia A patients, once-weekly subcutaneous administration of emicizumab was remarkably effective in preventing bleeding events, but the mechanisms controlling the regulation of emicizumab-mediated haemostasis remain to be explored. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…It has recently been shown that emicizumab-mediated FXa generation is downregulated by direct inactivation of FVa through the activated protein C pathway. 42 Supporting these assumptions, no thrombotic events were identified in HA patients without FVIII inhibitors receiving emicizumab prophylaxis in combination with repetitive FVIII infusions for the treatment of breakthrough bleeds or during surgery. 15 This may bring another argument for continuing emicizumab prophylaxis irrespective of the level of FVIII recovery detected in patients undergoing ITI.…”
Section: Emicizumab Prophylaxis Provides a Good Safety Profilementioning
confidence: 79%
“…It has recently been shown that emicizumab-mediated FXa generation is downregulated by direct inactivation of FVa through the activated protein C pathway. 42 Supporting these assumptions, no thrombotic events were identified in HA patients without FVIII inhibitors receiving emicizumab prophylaxis in combination with repetitive FVIII infusions for the treatment of breakthrough bleeds or during surgery. 15 This may bring another argument for continuing emicizumab prophylaxis irrespective of the level of FVIII recovery detected in patients undergoing ITI.…”
Section: Emicizumab Prophylaxis Provides a Good Safety Profilementioning
confidence: 79%
“…15 Emicizumab does not inhibit the regulatory effect of TFPI and antithrombin. 16 Furthermore, emicizumab-driven thrombin generation is downregulated by activated protein C through inactivation of activated factor V. 17 These in vitro data indicated that emicizumab procoagulant activity can be regulated by the natural anticoagulation system.…”
Section: Preclinical Development Of Emicizumabmentioning
confidence: 97%
“…40 Despite emicizumab's insusceptibility to activated protein C, inhibition of FVa therewith as well as inhibitory activities of tissue factor pathway inhibitor (TFPI) and antithrombin seem to regulate the procoagulant activity of emicizumab well enough. 41,42 In clinical trials, emicizumab was administered prophylactically once a week, every other week or every four weeks, and these three regimens have been used post-licensure. 33,34,[43][44][45] In HAVEN 1 and 3 studies, the drug reduced bleeding rates in persons with hemophilia A with and without FVIII inhibitors by 79 and 68% compared to pre-emicizumab prophylaxis with standard bypassing agents (aPCC and rFVIIa) and FVIII, respectively.…”
Section: Emicizumab: Fviiia In Disguise Of An Antibodymentioning
confidence: 99%